INTEGRASI NILAI-NILAI KARAKTER BANGSA DALAM PEMBELAJARAN IPS DI MTS SABILUL MUTTAQIEN BATANGHARI - Sholiha , Sangidatus (STKIP PGRI Bandar Lampung, 2021)
The inculcation of integrated character values ​​in learning activities. Learning activities are interactive activities between teachers and students that have educational value. These activities are directed to achieve the goals that have been planned systematically before teaching is carried out. This study uses a qualitative descriptive approach, which describes the process of integrating the values ​​of the nation's character in social studies learning in class VIII at MTs Sabilul Muttaqien based on the perspective of Gagne's theory. Learning based on Gagne's perspective takes place in four phases, namely the apprehending phase, the acquisition phase, the storage phase and the retrieval phase. The Apprehending Phase in inculcating character values ​​in social studies learning is that the teacher provides a stimulus to students so that learning can attract the attention of students. The acquisition phase in inculcating character values ​​in learning is the teacher's process of linking the previous material with the material to be taught to help students remember the material that has been taught. In this storage/retention phase, the teacher provides exercises so that students can repeat and use their new knowledge at any time, creating pleasant learning conditions that support the learning process, habituation. Retrieval Phase in planting character values ​​in learning, namely what is learned, owned and stored in memory can be used to solve problems faced by students.